Solving a nonhomogeneous integral equation with the variable lower limit - Kosmakova, M.T.; Akhmanova, D.M.; Tuleutaeva, Zh.M.; Kasymova, L.Zh. (KSU publ., 2019)
An nonhomogeneous integral equation with a singular kernel is considered. A feature of the equation under study is the incompressibility of the integral operator. In the study of the equation, an auxiliary simpler equation is used with the right-hand side equal to 1. The incompressibility of the integral operator for the equation under study is shown. Using the relations for an independent variable, the equation is equivalently reduced to a certain simplified equation. With the help of replacements for independent variables, the equation is reduced to an integral equation with a difference kernel. By applying the Laplace transform, the obtained equation is reduced to an ordinary first-order differential equation (linear). Its solution is found. By using the inverse Laplace transform, a solution of the auxiliary integral equation is obtained in the form of a convergent series in some domain. The solution of the initial equation with an arbitrary right-hand side is written through the solution of the auxiliary equation.
Keywords: nonhomogeneous singular integral equation; auxiliary equation; Laplace transform; convergent series